Study of tellis-coded modulation - Yu, Yi (Nanyang Technological University, 2020)
Trellis Coded Modulation (TCM), also known as nonbinary convolutional coded modulation, is normally applied in telecommunication to transmit information with high efficiency over bandlimited channels. A software application, such as Octave or MATLAB, is required to plot graphs for BPSK and 8-PSK with TCM technology. The overall summary to implement this project as such. During the 2nd semester of the third year in NTU, my task is to study on how to use Octave or MATLAB, and try to understand BPSK deeper so that I can try to plot graph via Octave or MATLAB. In the special term, my target is to understand what is rational of bit error rate (BER) for BPSK, in the meanwhile, I am going to study how to plot BER for BPSK modulation in Octave or MALAB. Moving to the first semester of the fourth year, I need to get the knowledge for trellis-coded modulation (TCM) and understand how this modulation can reduce BER of probability for BPSK modulation. At the end of this semester, I need to produce graphical representations by using TCM in Octave or MATLAB. Throughout the second semester of the fourth year in NTU, it is required to write professional script files to compute BER as much as possible and the final report of this project is arranged to submit this semester.